Production and economic risk analysis of pig fattening - Soltész, Angéla (Acta Agraria Debreceniensis, 2014)
I prepared a “model farm” producing fattening pigs in order to examine the main risk of production and market factors affecting the profitability of fattening pig production. Values of body weight (at the beginning of fattening and at the end of fattening), mortality rate, feed conversion ratio (FCR) of fattening pig as well as the main cost and price data were recorded as the input data of the model. Production value per unit, production cost per unit and income per unit were used as output. The Monte-Carlo simulation was used in the model for risk assessment. Based on the results of the analysis, it was concluded that the production value per unit was most affected by the selling price of fattening pig (ß=0.972), the production cost per unit were most influenced by the body weight at the beginning of fattening (ß=0.567) and the feed conversion ratio (ß=0.537), in addition, the change of the income per unit was most determined by the previously factors.